LECTURER PROFESSIONAL DEVELOPMENT (Case studies in three state-owned colleges in Bandung, West Java, Indonesia) - Syaodih, Ernalia Lia (International Journal of Education, 2011)
This study is aimed at investigating policy, design, implementation, evaluation,and supporting as well as discouraging factors which inhibit the lecturers’ competencedevelopment in three state-owned colleges in Bandung, West Java, indonesia. The studyalso attempts to propose a model for lecturer professional competency development. Thestudy reveals that policy and development programs towards the betterment of lecturerprofessional competency exist in the three institutions. Programs for lecturer competencydevelopment are generally in line with the so called Strategic Plans of the Faculty orDepartment and are based mainly on the internal conditions of the institutions. Theprograms, are, among others, support for lecturers’ further study (Master’s or Doctoralprogram at home or overseas), or participation in short courses, academic activitiessuch as discussion, seminars, workshops, and individual studies through various kindsof research. Those activities are useful for the lecturers to enhance their professionalcompetencies, including pedagogic, professional, personal, and social competencies.The study also suggests that in implementing these programs, there are some factorswhich support as well as those which hinder the realisation of the programs. Supportingfactors include development projects funded by the Ministry of Education, grants offeredby the institution in collaboration with the lecturer development program, supportsfrom the units within the institution, and the lecturers’ motivation to enhance their owncompetency on their own expense. Meanwhile, hindrances include the very limitednumber of opportunities given to the lecturers to participate in different activities that canpromote their professional competencies, limited financial support from the Ministries,and work load.Key words: Lecturer Professional Development, higher education